How European is European private international law?: Sources, court practice, academic discourse - Hein, Jan von; Kieninger, Eva-Maria; Rühl, Giesela (Intersentia, 2019)
Over the course of the last few decades, the European legislature has adopted a total of 18 Regulations in the area of private international law, including civil procedure. The resulting substantial legislative unification has been described as the first true 'Europeanisation' of private international law, and even as a kind of 'European Choice of Law Revolution'. However, it remains largely unclear whether the far-reaching unification of the 'law on the books' has turned private international law into a truly European 'law in action': To what extent is European private international law actually based on uniform European rules common to all Member States, rather than on state treaties or instruments of enhanced cooperation? Is the manner in which academics and practitioners analyse and interpret European private international law really different from previously existing domestic approaches to private international law? Or, rather, is the actual application and interpretation of European private international law still influenced, or even dominated, by national legal traditions, leading to a re-fragmentation of a supposedly uniform body of law? In bringing together academics from all over Europe, How European is European Private International Law? sets out to answer - for the first time - these crucial and interrelated questions. It sheds light on the conspicuous lack of 'Europeanness' currently symptomatic of European private international law and discusses how this body of law can become truly European in character in the future. With contributions by Jürgen Basedow (Max Planck Institute for Comparative and International Private Law), Paul Beaumont (University of Sterling), Sabine Corneloup (University Paris II, Panthéon-Assas), Gilles Cuniberti (University of Luxembourg), Agnieska Frackowiak-Adamska (University of Wroclaw), Stéphanie Francq (University of Louvain), Pietro Franzina (University of Ferrara), Jan von Hein (University of Freiburg), Michael Hellner (Stockholm University), Eva-Maria Kieninger (University of Würzburg), Thomas Kadner Graziano (University of Geneva), Xandra Kramer (Erasmus University Rotterdam), Johan Meeusen (University of Antwerp), Pedro A. de Miguel Asensio (Complutense University Madrid), Dário Moura Vicente (University of Lisbon), Marta Requejo Isidro (Max Planck Institute for Procedural Law Luxembourg), Giesela Rühl (University of Jena), Alix Schulz (Heidelberg University) and Marc-Philippe Weller (Heidelberg University).